2014
DOI: 10.1111/eea.12219
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing speciation within the Anastrepha fraterculus cryptic species complex: the case of the Andean morphotype

Abstract: The Anastrepha fraterculus (Wiedemann) (Diptera: Tephritidae) cryptic species complex is currently composed of seven taxonomically recognized morphotypes. Both, pre‐ and post‐zygotic isolation has been documented among four of these morphotypes, revealing that in fact they appear to be distinct biological entities. In order to progress in the full delimitation of species within the complex, we examined reproductive isolation between a Colombian population of the Andean morphotype and populations belonging to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 39 publications
(108 reference statements)
6
59
0
2
Order By: Relevance
“…Therefore, the Sibiraea complex may be on an incomplete process of speciation. Ongoing speciation has been reported in several taxa such as the Gymnocypris complex in the QTP (Zhang et al, 2013) and the Anastrepha fraterculus complex in the Americas (Devescovi et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the Sibiraea complex may be on an incomplete process of speciation. Ongoing speciation has been reported in several taxa such as the Gymnocypris complex in the QTP (Zhang et al, 2013) and the Anastrepha fraterculus complex in the Americas (Devescovi et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Since then, other findings from distinct populations along its distributional range were reported supporting this hypothesis, such as differences of karyotypes (Mendes 1958, Bush 1962, Solferini and Morgante 1987, Selivon et al 2005b); isozyme divergence (Morgante et al 1980, Steck 1991); DNA sequences (Steck and Sheppard 1993, Smith-Caldas et al 2001); or studies with multiple approaches including karyotype, isozymes, and morphology (Selivon and Perondini 1998, Selivon et al 2004, 2005a). Moreover, differences in host range and pest status (Baker 1945, Aluja et al 2003, Hernández-Ortiz and Morales-Valles 2004, Zucchi 2007); reproductive isolation and sexual incompatibilities (Selivon et al 1999, 2005a, Vera et al 2006, Cáceres et al 2009, Rull et al 2013, Devescovi et al 2014); or data on pheromone composition and cuticular hydrocarbon profiles (Břízová et al 2013, Vaníčková et al 2015). …”
Section: Introductionmentioning
confidence: 99%
“…It is widely distributed in America and is associated with a large number of host fruits (Hernández-Ortiz et al 2012, Norrbom et al 2013). In fact, this nominal species comprises a cryptic species complex, as has been demonstrated by genetic (Steck 1991, Steck and Sheppard 1993, Smith-Caldas et al 2001) and cytogenetic (Selivon et al 2004, 2005, Goday et al 2006) studies, reproductive isolation tests (Selivon et al 1999, Vera et al 2006, Cáceres et al 2009, Devescovi et al 2014), chemo-taxonomy (Cáceres et al 2009, Břízová et al 2013, Vaníčková et al 2015) and morphological (Selivon and Perondini 1998, Selivon et al 2005, Hernández-Ortiz et al 2004, 2012) analysis. Based on adult morphology, Hernández-Ortiz et al (2012) identified seven morphotypes within this complex: Mexican, Andean, Venezuelan, Peruvian, and three morphotypes from the Brazilian territory, one of which extends to Argentina.…”
Section: Introductionmentioning
confidence: 80%